The Mach-Zehnder interferometer: Examination of a volume by non-classical localization plane shifting - Simon, Juan Miguel (2001)
The Mach-Zehnder interferometer can be used as is customary in optical testing but, to examine different layers of a volume, the procedure of either readjusting the interferometer or displacing the specimen can be avoided, employing an incoherent periodic source. In this case, leaving the specimen in a fixed position and without readjusting the interferometer, the different layers can be analysed, shifting a non-classical localization plane by a change in the source period. In this paper experimental interferograms, obtained by varying this period to map the disturbances present on either one or both faces of a phase object, are shown.